Hypertension in the absence of urinary abnormalities – an unusual presentation of anaphylactoid purpura - Thong, Pui Lin; How, Kang Nien; Bakrin, Ikmal Hisyam (Malaysian Medical Association, 2020)
Henoch-Schonlein Purpura (HSP) or anaphylactoid purpura, currently named IgA vasculitis is the most common form of systemic vasculitis in children. In adults and young infants, HSP tends to have atypical presentations with higher rates of severe gastrointestinal problems and delayed renal complications. While hypertension is a known complication of HSP nephritis, it is rarely seen in individuals with normal renal function and urinary findings. We report a case of a 7-year-old boy with HSP, who presented with abdominal pain and severe hypertension without other features of glomerulonephritis.